Decision Support for Natural Disasters and Intentional Threats to Water Security - Illangasekare, Tissa; Mahutova, Katarina; Barich, John J. (NATO Science for Peace and Security Series C: Environmental Security, 2009)
The NATO Advanced Research Workshop, "Decision Support for Natural Disasters and Intentional Threats to Water Security" was the result of close collaboration between environmental, security, water resource, and health officials in the United States and Croatia. The premise of the Workshop is that multiple, disparate threats to water security exist, and that shared decision support structures provide effective means for avoiding and responding to potential or actual situations. The Workshop was co-directed by Professors Tissa Illangasekare of the Colorado School of Mines, and Dragutin Geres of Hrvatske vode. The Workshop was organized into a series of case studies, presentation of management tools, or a combination of the two. Presentations were further organized as to (1) Natural Occurrences, (2) Anthropogenic Causes, and (3) Decision Support Tools. Delegates from eleven countries assembled to explore these topics at the Hotel Dubrovnik President in Dubrovnik from April 22-25, 2007. A total of thirty delegates from NATO, Partner, Mediterranean Dialog, or other countries were in attendance. The final program included technical sessions using a presentation and dialog format, a field trip, and networking sessions. There were twenty five technical presentations supported by seventeen formal papers (many updated in late-2008 and 2009), and these form the basis for these proceedings. xi ACKNOWLEDGEMENTS The co-directors and organizers of this Advanced Research Workshop a- nowledge the NATO Science Programme for major financial support and for providing detailed guidance on how best to organize and execute a meeting of this nature.